2017
DOI: 10.1111/acem.13305
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Emergency Medicine Educational Research: The Best Publications of 2015

Abstract: This installment in this critical appraisal series reviews 12 of the highest-quality EM-related medical education research manuscripts published in 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In 2016, there continued to be a trend toward increasing number of articles that meet our a priori criteria for full review ( n = 75) compared with 2015 ( n = 61) and 2014 ( n = 25) . As the field of medical education continues to grow, we expect that this trend will continue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, there continued to be a trend toward increasing number of articles that meet our a priori criteria for full review ( n = 75) compared with 2015 ( n = 61) and 2014 ( n = 25) . As the field of medical education continues to grow, we expect that this trend will continue.…”
Section: Discussionmentioning
confidence: 99%
“…In this ninth installment of the annual critical appraisal of the EM education research, we systematically analyze and rank the best publications of 2016. We used modified previously published criteria for qualitative and quantitative research studies similar to prior installments of this series . We also describe and summarize current trends in medical education research over the past year as they relate to EM learners and educators.…”
mentioning
confidence: 99%
“…External funding has been shown to be a crucial step toward the maturation of successful investigators and increasing the knowledge base complexity of publications . One series of articles evaluating EM education research found that the number of funded studies increased from 16% in 2014 to 20% in 2015, although this declined to 11% in 2016 . We conducted a review of all publications from 2018 and 2019 in AEM Education and Training and found that 34% of original manuscripts had reported some form of funding.…”
Section: Advances In Medical Education Scholarshipmentioning
confidence: 94%
“…Additionally, there has been an overall increase in the quality of education research and expectations from EM and other fields . As consumers of research, educators are looking for more rigorous methods and conceptual frameworks in published research .…”
Section: Advances In Medical Education Scholarshipmentioning
confidence: 99%